2019
DOI: 10.2478/ttj-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

One Belt And One Road: Literature Analysis

Abstract: In the late 2013 One Belt and One Road (OBOR) was announced in Chinese international political speeches. Thereafter, this significant investment program started and research works were also initiated. We found that first journal publications (in English) appeared in 2016, and thereafter their amounts have increased, especially in 2018. Most of the contributing authors are China based or Chinese scholars living in abroad. Highest citations amounts are for the works published in the first analysis year, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The initiative is strongly tied to the person of President Xi. However, the BRI is not a strategy in the strict sense of the word because it has no centrally defined goal, and there is no timeframe allocated to it (Li-Hilmola, 2019).…”
Section: Domestic Source Of Accommodationmentioning
confidence: 99%
“…The initiative is strongly tied to the person of President Xi. However, the BRI is not a strategy in the strict sense of the word because it has no centrally defined goal, and there is no timeframe allocated to it (Li-Hilmola, 2019).…”
Section: Domestic Source Of Accommodationmentioning
confidence: 99%
“…The original, "Silk Road" was an ancient network of trade routes formally established over 2100 years ago during the Han Dynasty (206 BC-24 AD) to promote trade, peace, cooperation, cultural developments, mutual learning, and bene ts essential for increasing developments and prosperity among China, Asia, Africa, and Europe, it spanned over 7000km [22]. Trung et al [23] explained that the vision of the "New Silk Road", or "One Belt, One Road" (OBOR) is determined to take a major step in leading the trends in globalization in the 21st Century.…”
Section: The Initiative: a Glimpse Into China's Strategymentioning
confidence: 99%
“…He added that the Sino-African connections date back to the Han dynasty (206 BC to 220 AD), pursuing through the Tung, Song, and Ming dynasties. The expansion in trade between China and Africa was con rmed [22] and noted that trade between China and Africa stood at US$935 million in 1990, and then accelerated to US$55.5 billion in 2000 [46,47]. Other studies reported that from 2001, Africa's exports to China jump up at an annual rate of over 40% to reach US$28.8 billion in 2006, while in the same year (2006) Africa's imports from China quadrupled to US$26.7 billion [16].…”
Section: China-africa Trade Relationsmentioning
confidence: 99%